Learning Methods Of Prayer Worship For First Class Elementary School - Muhammad Nawawi Ginting; A. Rahmat Rosyadi; Ibdalsyah Ibdalsyah (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2022)
Prayer is an act of worship that is commanded by Allah to all those who profess their faith. Even prayer is said to be the pillar of religion, a practice that will first be accounted for. So it is fitting that prayer learning should be something that is important to be taught in the world of education, the teaching of learning to pray this must be taught as early as possible so that it becomes habituation and understanding so that when you are an adult you need to think twice when you want to leave prayer. Moreover, there has been an understanding that prayer is an obligation which if left behind is a sin. Even so, there is a need for a precise and effective method to provide such learning to early childhood children who in fact have not yet matured their way of thinking and the prayer command has not yet become a mandatory command to do. For this reason, this research is here to provide a solution about the method of learning prayer worship in grade 1 elementary school. In this study, the authors limit the research problem to only the method of learning to pray in the 1st grade of elementary school. The research method used is library research. This is done so that the study can be more in-depth using literature observation techniques, documentation of research data, both primary and secondary. The results obtained in this study are the learning methods of prayer worship in grade 1 Elementary School, namely the demonstration method, the question and answer method and the habituation method with the stages and implementation of their application. These three methods are not mutually exclusive methods.